1998
DOI: 10.1002/(sici)1096-8628(19980106)75:1<109::aid-ajmg22>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical-radiological and molecular findings in hypochondroplasia

Abstract: Hypochondroplasia is an autosomal dominant skeletal dysplasia characterized by disproportionate short stature. A mutation (N540K) in the fibroblast growth factor receptor 3 (FGFR3) gene was described in some patients with this condition. The aims of the study were to identify the frequency of the FGFR3 gene mutation, to define the salient clinical and radiological abnormalities of the affected subjects, and to verify the contribution of molecular findings to the clinical and radiological definition of hypochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 13 publications
3
39
0
1
Order By: Relevance
“…Five mutations result in speci®c cysteine substitutions in FGFR3 (R248C, S249C, G370C, S371C, Y373C), six mutations eliminate the stop codon and result in 141-amino acid C-terminal extension (J807G, J807R, J807L, J807C l[2421ApT], J807C [2421ApC], J807W), and one mutation leads to a K650M substitution in FGFR3 (Rousseau et al, 1995;Tavormina et al, 1995;Bonaventure et al, 1996;Rousseau et al, 1996a;Bellus et al, 1997;Kitoh et al, 1998;Wilcox et al, 1998;Passos-Bueno et al, 1999). The majority of cases Coronal synostosis, speci®c bone anomalies of the hands and feet, but without any of classical craniosynostosis syndromes P250R (Pro250Arg) C-AN Shallow orbits, proptosis, craniosynostosis, maxillary hypoplasia, and acanthosis nigricans A391E (Ala391Glu) TD1, thanatophoric dysplasia type I (Rousseau et al, 1995;Tavormina et al, 1995;Bonaventure et al, 1996;Rousseau et al, 1996a;Bellus et al, 1997;Kitoh et al, 1998;Wilcox et al, 1998;Passos-Bueno et al, 1999); TD2, thanatophoric dysplasia type II (Tavormina et al, 1995;Wilcox et al, 1998); ACH, achondroplasia (Rousseau et al, 1994;Bellus et al, 1995a;Ikegawa et al, 1995); HCH, hypochondroplasia (Bellus et al, 1995b;Prinos et al, 1995;Rousseau et al, 1996b;Deutz-Terlouw et al, 1997;Grigelioniene  et al, 1998;Prinster et al, 1998); PLSD-SD, platyspondylic lethal skeletal dysplasia, San Diego type (Brodie et al, 1999;Passos-Bueno et al, 1999); SADDAN, severe achondroplasia with developmental delay and acanthosis nigricans (Tavormina et al, 1999); NCS, non-syndromic craniosynostosis (Bellus et al, 1996;Muenke et al, 1997); C-AN, Crouzon with acanthosis nigricans <...>…”
Section: Discussionmentioning
confidence: 99%
“…Five mutations result in speci®c cysteine substitutions in FGFR3 (R248C, S249C, G370C, S371C, Y373C), six mutations eliminate the stop codon and result in 141-amino acid C-terminal extension (J807G, J807R, J807L, J807C l[2421ApT], J807C [2421ApC], J807W), and one mutation leads to a K650M substitution in FGFR3 (Rousseau et al, 1995;Tavormina et al, 1995;Bonaventure et al, 1996;Rousseau et al, 1996a;Bellus et al, 1997;Kitoh et al, 1998;Wilcox et al, 1998;Passos-Bueno et al, 1999). The majority of cases Coronal synostosis, speci®c bone anomalies of the hands and feet, but without any of classical craniosynostosis syndromes P250R (Pro250Arg) C-AN Shallow orbits, proptosis, craniosynostosis, maxillary hypoplasia, and acanthosis nigricans A391E (Ala391Glu) TD1, thanatophoric dysplasia type I (Rousseau et al, 1995;Tavormina et al, 1995;Bonaventure et al, 1996;Rousseau et al, 1996a;Bellus et al, 1997;Kitoh et al, 1998;Wilcox et al, 1998;Passos-Bueno et al, 1999); TD2, thanatophoric dysplasia type II (Tavormina et al, 1995;Wilcox et al, 1998); ACH, achondroplasia (Rousseau et al, 1994;Bellus et al, 1995a;Ikegawa et al, 1995); HCH, hypochondroplasia (Bellus et al, 1995b;Prinos et al, 1995;Rousseau et al, 1996b;Deutz-Terlouw et al, 1997;Grigelioniene  et al, 1998;Prinster et al, 1998); PLSD-SD, platyspondylic lethal skeletal dysplasia, San Diego type (Brodie et al, 1999;Passos-Bueno et al, 1999); SADDAN, severe achondroplasia with developmental delay and acanthosis nigricans (Tavormina et al, 1999); NCS, non-syndromic craniosynostosis (Bellus et al, 1996;Muenke et al, 1997); C-AN, Crouzon with acanthosis nigricans <...>…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of the SHOX gene have been described in patients with DCO and also in some cases of idiopathic short stature with mild rhizomelic body disproportions (Belin et al 1998;Rao et al 1997;Shears et al 1998). The mutations responsible for HCH in 40-70% of the cases are found in the FGFR3 gene (Bellus et al 1995;Bonaventure et al 1996;Prinos et al 1995;Prinster et al 1998;Ramaswami et al 1998). …”
Section: Discussionmentioning
confidence: 99%
“…A characteristic feature of DCO is a forearm deformity, Madelung deformity, which has a varying degree of severity and is often absent in early childhood. Point mutations and deletions of the short stature homeobox containing gene (SHOX) have been described in DCO and idiopathic short stature with mild rhizomelic body disproportion (Belin et al 1998;Ogata 1999;Rao et al 1997;Shears et al 1998), while 40-70% of the HCH cases have the Asn540Lys mutation in the fibroblast growth factor receptor 3 (FGFR3) gene (Bellus et al 1995;Prinos et al 1995;Prinster et al 1998;Ramaswami et al 1998). It has been suggested that HCH individuals without the Asn540Lys substitution in the FGFR3 gene are less disproportionate (Ramaswami et al 1998;Grigelioniene et al 2000), indicating that these cases might have a phenotype resembling idiopathic short stature or mild cases of DCO without Madelung deformity.…”
Section: Giedre Grigelioniene · Ole Eklöf · Sten Anders Ivarsson · Otmentioning
confidence: 99%
“…In addition to the most common p.N540K HCH mutation, other mutations have been reported to be associated with a milder phenotype with less severe disproportion, no macrocephaly, and minor radiologic abnormalities (19,20,21). Mild forms have been described, especially where specific mutations in the p.K650 codon are involved (22).…”
Section: Discussionmentioning
confidence: 99%